Healthy Semi Automatic Grill Machine - borirak, theerapong (Srinakharinwirot University Engineering Journal, 2019)
The objective of this research aimed to develop low smoke and scent roasting food process by design and fabricate a healthy semi - automatic grill machine. The machine made by 304 stainless steel with dimension of 60 cm width, 90 cm length and 45 cm height. In the machine installed 4 sets of infrared heaters with the reflector total electrical power 2,400 W of the infrared heaters. A stainless chain conveyor with the jigs used for carrying roasted meat sticks. The chain conveyor transports meat to grill. The chain conveyor system features elliptical motion pass infrared heaters roasted meat sticks. The chain conveyor is set perpendicular to the ground and a series of infrared heaters are placed parallel to roasted meat sticks the prevent the smoke from the grill. The sticks of meat are released from the chain conveyer to the tray to distribute products after grill process. The machine used the 12 V DC motor for driving the conveyor gear 3 revolution speeds 0.32 rpm, 0.24 rpm and 0.19 rpm. The infrared heater temperature control is set at 210 - 240°C. The 5 samples of materials for testing are pork with sauce, pork with milk and sauce, pork satay, chicken and beef. The thermal efficiency depends on the size and weight of the meat. The healthy semi - automatic grill machine can make production rate 80 – 500 pieces of grill meat per hour. The average electricity consumption of the machine is 2.21 kWh. The machine can reduce energy costs by 13.4 percent compared to the use of charcoal production.